Prevalence of Anxiety among Pregnant Women Attending Antenatal care in Jordan: A Single Center Study - Basha, Asma; Sabanekh, Caroline; Shlash, Laith; Dawod, Lujain; Dweik, Murad; Obeidat, Mohammed; Malkawi, Lna; AlRyalat, Saif (Jordan Journal of Pharmaceutical Sciences, 2021)
Background: Pregnancy is a stressful physiological period, where some women may suffer from some degree of anxiety. Our aim is to study the prevalence of anxiety among pregnant women attending routine antenatal care clinics. Methodology: This was a cross sectional study for pregnant women coming for their routine antenatal care at Jordan University Hospital, during the period from October 1st to 27th, 2019.They were interviewed while waiting for their turn by a trained 6th year medical student using the Generalized Anxiety Disorder -7 (GAD-7) questionnaire. Results: A total of 200 women were interviewed with a mean age of 30 ± 5.3years, ranges between (18 and 45years). Their gravidity mean was 3.3±2.9 (ranges from 0-22) and their mean parity was 1.6 ± 1.4. 59 women (29.5%) had previous history of miscarriage. Number of miscarriages ranged from 1 to 12 with a mean of 2.5 ± 3.3.In our study, 66 (33.0%) women had moderate and 42 (21.0%) had severe symptoms. For women with history of previous miscarriages, there was no significant correlation with anxiety, except for those with recurrent miscarriages (p-value= 0.019). Conclusions: Recurrent miscarriage can affect women’s psychological well-being; with an increase in the possibility of experiencing anxiety. Implementing mental health assessment in antenatal care has long-lasting benefits for both mother and infant.